Perspektif Suku Timor Soe Tentang Manusia Menurut Ume Kbubu (RUMAH BULAT) - Christofel Saetban; Dunosel Ir. Koebanu (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
Research highlights the close relationship between humans and culture, especially in the context of Indonesia's indigenous tribes. The Timor Soe tribe, who inhabit the West Timor region, have unique traditions and views on life that are reflected in the design and symbolism of Ume Kbubu. This research aims to determine the perspective of the Timor Soe Tribe about humans through the symbolism and meaning of the traditional ume kbubu house. The research method used is a literature study with a qualitative approach to collect and analyze data from various literature sources. The research results show that Ume Kbubu not only functions as a place to live, but also as a symbol of the cultural and spiritual identity of the Timor Soe Tribe. This house depicts the social, moral, religious and political values ​​that are important in the life of the tribe. The Timor Soe Tribe's perspective on humans emphasizes a holistic relationship between humans and nature, where balance and respect for the environment are the main principles. The implications of this research show that an in-depth understanding of the cultural perspective of the Timor Soe Tribe can provide valuable insight into efforts to preserve culture and environmental sustainability. The values ​​of sustainability and balance adhered to by this tribe are relevant in facing current global challenges, such as climate change and environmental degradation. Thus, this research emphasizes the importance of maintaining and valuing cultural diversity as an integral part of human identity and sustainability.